2000
DOI: 10.1002/1096-8628(20001218)95:5<425::aid-ajmg3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Absence of 9q22-9qter in trisomy 9 does not prevent a Dandy-Walker phenotype

Abstract: We report on a female fetus with partial trisomy 9 due to a reciprocal translocation in the mother. Routine ultrasound examination at 23 weeks showed hypoplasia of the cerebellar vermis, dilated foramen Magendii, and dilatation of the cisterna magna. Due to the poor prognosis, the parents opted for termination of pregnancy. A postmortem examination confirmed caudal hypoplasia and dysplasia of the cerebellar vermis, resulting in a massively dilated foramen Magendii through which the enlarged cisterna magna comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
(14 reference statements)
1
8
0
2
Order By: Relevance
“…There have been at least 20 case reports on DWS cases complicated by trisomy 9 (Golden & Schoene 1993). These reports include cases complicated by DWS such as trisomy 9 mosaic syndrome (Bureau et al 1993;Tarani et al 1994;Murru et al 2002), partial trisomy 9 (Zacharias et al 1983;Hannam et al 1999;von Kaisenberg et al 2000;Chen et al 2002aChen et al , 2005Metzke-Heidemann et al 2004), tetrasomy 9p (Melaragno et al 1992;Cazorla et al 2003;Hengstschlager et al 2004), and complete trisomy 9 (McDuffie 1994). The number of these reports shows that DWS can be commonly encountered in chromosome 9.…”
Section: Chromosome 9 and Dwsmentioning
confidence: 99%
“…There have been at least 20 case reports on DWS cases complicated by trisomy 9 (Golden & Schoene 1993). These reports include cases complicated by DWS such as trisomy 9 mosaic syndrome (Bureau et al 1993;Tarani et al 1994;Murru et al 2002), partial trisomy 9 (Zacharias et al 1983;Hannam et al 1999;von Kaisenberg et al 2000;Chen et al 2002aChen et al , 2005Metzke-Heidemann et al 2004), tetrasomy 9p (Melaragno et al 1992;Cazorla et al 2003;Hengstschlager et al 2004), and complete trisomy 9 (McDuffie 1994). The number of these reports shows that DWS can be commonly encountered in chromosome 9.…”
Section: Chromosome 9 and Dwsmentioning
confidence: 99%
“…[67] The bilateral ventriculomegaly and an enlarged cistern magna reported in fetus with partial trisomy 9 (pter → q22) and partial trisomy 21(q22.3- qter). [8] vonKaisenberg et al [9] reported a Dandy-Walker malformation and hypoplasia of the cerebellar vermis in a fetus with partial trisomy 9 and 7. Recently partial trisomy 9p (p 11.2 → pter) reported in a fetus with Dandy-Walker malformation and it was suggested that the 9 pter → 11.2 region critical for the development of Dandy-Walkermalformation and ventriculomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…El cuadro clínico se caracteriza por fascie típica que incluye microcefalia, enoftalmo, hipertelorismo, puente ancho nasal, fisura palpebral entre otros; retardo mental; alteraciones cerebrales principalmente de la línea media; restricción del crecimiento; hipoplasia ungueal; hipotonía; y otras manifestaciones que comprometen esqueleto, corazón, riñón y genitales (12,14,15), la gran mayoría descrita en nuestro caso anteriormente.…”
Section: Discusionunclassified
“…También se ha descrito otras anormalidades como gliosis moderada, anormalidades del hipocampo, atrofia del cuerpo calloso, ventriculomegalia, hipoplasia del vermis cerebeloso, siringomielia y mielomeningocele (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discusionunclassified